20 Combined high-resolution stress perfusion and scar assessment in patients with ischaemic heart failure. (May 2018) - Villa, Adriana DM; Sammut, Eva; Giovine, Gabriella Di; Lee, Jack; Ryan, Matthew; Alfakih, Khaled; Pavlopoulos, Harry; Scannell, Cian; Milidonis, Xenios; Perera, Divaka; Ismail, Tevfik; Razavi, Reza; et al.
Abstract : Introduction: Myocardial scar and ischaemia frequently coexist in patients with ischaemic heart failure (IHF). In clinical practice, stress-perfusion (SP) is assessed visually together with late gadolinium enhancement (LGE) images, however the feasibility of simultaneous LGE and SP quantification has only been recently demonstrated (Villa, JCMR 2016). The aim of this study was to apply a fully quantitative method combining scar and perfusion to the challenging cohort of patient with IHF. Methods: Consecutive patients with IHF (LVEF <45%) were included. All patients underwent high-resolution k-T adenosine SP at 3 T (Philips Achieva) with a dual-bolus approach and invasive coronary angiography. Visual assessment was performed by two expert operators, blinded to clinical information. Quantification was performed with a semi-automated approach, using validated high-resolution deconvolution analysis and conventional semi-quantitative LGE analysis (5SD). High-resolution SP, LGE and fusion maps were then generated. Ischaemic burden was calculated with and without LGE. Results: 161 patients were included (LVEF 33.5±9.8). 93% had evidence of flow-limiting CAD on angiography, 42.9% demonstrated three-vessels disease. The ischaemic burden detected with visual assessment (9.4%) was significantly lower compared to the ischaemic burden detected with quantitative methods. Moreover, there was an overestimation when not considering LGE. Visual assessment underestimates the extent of ischaemia; quantitative high-resolution combined method correctly identifies more patients as having three-vessel disease. The methods were tested against invasive coronary angiography and there was evidence of a better performance of the quantitative methods on a per-patient level, with a significantly better performance of quantitative combined high-resolution on a per-vessel level. Conclusion: Our study showed that a fully quantitative approach enables accurate assessment of the ischaemic burden, without overestimation due to LGE, and that with this method we identify more patient with ischaemia in all coronary territories. Moreover, this study demonstrated that visual assessment, which is used routinely in clinical practice, tends to underestimate the extent of ischaemic in patient with IHF. In conclusion, high-resolution combined quantification should be used to avoid overlap between areas of scar and ischaemia, allowing a more precise assessment of the true ischaemic burden.